Pyroptosis regulation by Salmonella effectors - Meng, Yuan; Zhang, Qianjin; Xu, Mengen; Ding, Ke; Yu, Zuhua; Li, Jing (Frontiers in Immunology, 2024)
The genus Salmonella contains the most common foodborne pathogens frequently isolated from food-producing animals and is responsible for zoonotic infections in humans and animals.Salmonella infection in humans and animals can cause intestinal damage, resulting in intestinal inflammation and disruption of intestinal homeostasis more severe cases can lead to bacteremia.Pyroptosis, a proinflammatory form of programmed cell death, is involved in many disease processes.Inflammasomes, pyroptosis, along with their respective signaling cascades, are instrumental in the preservation of intestinal homeostasis. In recent years, with the in-depth study of pyroptosis, our comprehension of the virulence factors and effector proteins in Salmonella has reached an extensive level, a deficit persists in our knowledge regarding the intrinsic pathogenic mechanisms about pyroptosis, necessitating a continued pursuit of understanding and investigation. In this review, we discuss the occurrence of pyroptosis induced by Salmonella effectors to provide new ideas for elucidating the regulatory mechanisms through which Salmonella virulence factors and effector proteins trigger pyroptosis could pave the way for novel concepts and strategies in the clinical prevention of Salmonella infections and the treatment of associated diseases.